PENGARUH INFLASI DAN TINGKAT SUKU BUNGA TERHADAP HARGA SAHAM STUDI KASUS PADA PERUSAHAAN SEKTOR TEKNOLOGI SUBSEKTOR SOFTWARE & IT SERVICES YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020-2023 - SAIDAH, UMI (Universitas Tangerang Raya, 2024)
Umi Saidah, 2024 This study aims to analyze the influence of Inflation and Interest Rates on the Stock Price of Technology Sector companies, specifically the Software & IT Services subsector listed on the Indonesia Stock Exchange during the 2020-2023 period. This research is motivated by fluctuations in Stock Prices influenced by various macroeconomic factors, including Inflation and Interest Rates. Considering the importance of stocks as an investment instrument and as an indicator of a company’s health, a deep understanding, of the factors affecting Stock Price is crucial. The research method used is a quantitative approach with multiple linear regression. The data used in this study are secondary data obtained from company financial statements, Inflation data and Interest Rate data during the period under study. Data analysis techniques include descriptive statistical tests and classical regression assumption tests before performing regression analysis. The results of the study show that Inflation has a significant negative impact on Stocvk Prices, while Interest Rates do not have a significant effect on Stock Prices. These findings indicate the investors are more responsive to changes in Inflation compared to changes in Interest Rates in the context of Technology Sector Stoks in Indonesia. This research is expected to contribute to investors and policymakers in understanding stock market dynamics and the impact of macroeconomic factors on Stock Prices.